Collagen membranes for skin wound repair: A systematic review. (July 2021) - Araujo, Tiago Akira Tashiro; Almeida, Matheus Cruz; Avanzi, Ingrid; Parisi, Julia; Simon Sales, Abdias Fernando; Na, Yu; Renno, Ana
Membranes or skin dressing are common treatments for skin wound injuries, collagen being one the most effective materials for their manufacturing. Many different sources of collagen with diverse methods of extraction and processing have been used, with evidence of positive effects on the stimulation of skin wound healing. In spite of these factors, there is still limited understanding of the interaction between collagen membranes and biological tissues, especially due to the series of different types of collagen origin. In this context, this study aimed to conduct a systematic review of the available literature examining the effect of various collagen membranes for accelerating skin wound healing in experimental animal models and clinical trials. The present review was performed from March to May of 2020 searching in two databases (PubMed and Scopus). The following Medical Subject Headings (MeSH) descriptors were used: "collagen", "dressing", "membranes", "skin" and "wound". After the eligibility assessment, 16 studies were included and analyzed. The studies demonstrated that collagen was obtained predominantly from bovine and porcine sources, by acetic acid and/or enzyme dissolution. Additionally, most of the studies demonstrated that the membranes were processed mainly by freeze-drying or lyophilization methods. All the in vivo and clinical trial studies evidenced positive outcomes in the wound healing process, thus confirming that collagen membranes are one of the most efficient treatment for skin wounds, highlighting the enormous potential of this biomaterial to be used for skin tissue engineering purposes.